Answer:
Option B. ![R(2,4)](https://tex.z-dn.net/?f=R%282%2C4%29)
Step-by-step explanation:
we know that
If a ordered pair lie on the circle. then the ordered pair must satisfy the equation of the circle
step 1
Find the equation of the circle
we know that
The equation of the circle in center radius form is equal to
![(x-h)^{2}+(y-k)^{2}=r^{2}](https://tex.z-dn.net/?f=%28x-h%29%5E%7B2%7D%2B%28y-k%29%5E%7B2%7D%3Dr%5E%7B2%7D)
where
r is the radius of the circle
(h,k) is the center of the circle
substitute the values
![(x-6)^{2}+(y-1)^{2}=5^{2}](https://tex.z-dn.net/?f=%28x-6%29%5E%7B2%7D%2B%28y-1%29%5E%7B2%7D%3D5%5E%7B2%7D)
![(x-6)^{2}+(y-1)^{2}=25](https://tex.z-dn.net/?f=%28x-6%29%5E%7B2%7D%2B%28y-1%29%5E%7B2%7D%3D25)
step 2
Verify each case
case A) ![Q(1, 11)](https://tex.z-dn.net/?f=Q%281%2C%2011%29)
substitute the value of
in the equation of the circle and then compare the results
![(1-6)^{2}+(11-1)^{2}=25](https://tex.z-dn.net/?f=%281-6%29%5E%7B2%7D%2B%2811-1%29%5E%7B2%7D%3D25)
------> is not true
therefore
the ordered pair Q not lie on the circle
case B) ![R(2,4)](https://tex.z-dn.net/?f=R%282%2C4%29)
substitute the value of
in the equation of the circle and then compare the results
![(2-6)^{2}+(4-1)^{2}=25](https://tex.z-dn.net/?f=%282-6%29%5E%7B2%7D%2B%284-1%29%5E%7B2%7D%3D25)
------> is true
therefore
the ordered pair R lie on the circle
case C) ![S(4,-4)](https://tex.z-dn.net/?f=S%284%2C-4%29)
substitute the value of
in the equation of the circle and then compare the results
![(4-6)^{2}+(-4-1)^{2}=25](https://tex.z-dn.net/?f=%284-6%29%5E%7B2%7D%2B%28-4-1%29%5E%7B2%7D%3D25)
------> is not true
therefore
the ordered pair S not lie on the circle
case D) ![T(9,-2)](https://tex.z-dn.net/?f=T%289%2C-2%29)
substitute the value of
in the equation of the circle and then compare the results
![(9-6)^{2}+(-2-1)^{2}=25](https://tex.z-dn.net/?f=%289-6%29%5E%7B2%7D%2B%28-2-1%29%5E%7B2%7D%3D25)
------> is not true
therefore
the ordered pair T not lie on the circle